Process analytics : concepts and techniques for querying and analyzing process data /: concepts and techniques for querying and analyzing process data. ([2016]) - Beheshti, Seyed-Mehdi-Reza; Benatallah, Boualem; Sakr, Sherif, 1979-; Grigori, Daniela; Motahari-Nezhad, Hamid R; Barukh, Moshe Chai; Gater, Ahmed; Ryu, Seung Hwan
No abstract available